Use of the bicycle as a proposal to improve healthy living habits - Lizana Zora, Alejandro (2019)
The purpose of the present investigation was to determine to what extent the use of the bicycle influences the improvement of healthy life habits in Secondary Education students of the National College of UNHEVAL Application of the National Hermilio Valdizán University. A research of applied type of quasi-experimental design was developed, the study sample was constituted by 71 students of the sixth cycle of secondary education. The results show that with the use of the bicycle (x), the habits of healthy life were of positive influence. The results show improvement in relation to the practice of healthy lifestyle habits with the good use and handling of the bicycle (x). This situation is demonstrated by the hypothesis test that was favorable when rejecting the null hypothesis, with the value of Z = 8.74 is greater with respect to Z critical Zc = 1.64, which led to state that the use of the Bicycle positively influences the improvement of healthy living habits in students.